Pengetahuan Ibu Tentang Kartu Menuju Sehat (KMS) di Posyandu Wilayah Kerja Puskesmas Rawat Inap Sidomulyo Pekanbaru - Isnaniar; Norlita, Wiwik; Novrianti, Eno (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2023)
Monitoring the growth of toddlers is very important to know the existence of an early appeal. Toddler growth can be seen from the consideration every month is very necessary. Growth monitoring activities in Indonesia are carried out through monthly weighing at posyandu using a card to be healthy. Parents are encouraged to update the data on the card every month by taking their toddler to the posyandu or pediatrician. Monitoring a child's growth through this card can allow doctors to determine whether the child is growing normally according to his age or not. The Objective The aim of this study was to obtain an overview of mothers' knowledge about the card towards health at the Posyandu in the Working Area of the Sidomulyo Inpatient Health Center Pekanbaru. The type of research is descriptive. This research was carried out on August 15-20, 2022 at the Posyandu in the Working Area of the Sidomulyo Inpatient Health Center Pekanbaru. The population and sample in this study amounted to 50 people. The sampling technique used was the total sampling technique The instrument: used in this study is a questionnaire using a Likert scale, namely choosing one of two alternative answers with the subject's condition. The results of this study indicate that the mother's knowledge about the card towards healthy Pekanbaru Parental Knowledge Good 14 respondents (28.0%), Parental Knowledge Adequate 30 respondents (60.0%) and Parental Knowledge Less 6 respondents (12.0%). The Conclusion : In addition, it is recommended for mothers to pay more attention to the quality of their toddler's growth and for health workers to provide motivation for cadres to be able to provide correct information about cards to health.